A review of self-healable natural rubber based on reversible bonds: fundamental, design principle and performance - Mohd Kanafi, Nafeesa; Abdul Ghani, Anis; Abdul Rahman, Norizah; Abd Aziz, Azira; Sapuan Faris, S. M. (Springer New York, 2022)
Natural rubber is one of nature’s most exceptional materials due to its remarkable physicochemical properties. Comparing natural and synthetic rubbers, natural rubber possesses greater performance properties, such as green strength, tear strength, tensile strength, tensile modulus and toughness. Inspired by nature, self-healing materials are attractive materials due to the capability to automatically self-heal or self-repair when damage occurs. Self-healing natural rubber is a current evolution of elastomers that could offer new properties of recycling and reprocessing ability of rubber products for environmental conservation. Furthermore, it increases the value of natural rubber as a good sustainable material in daily life. Significant efforts have been made to develop high self-healing efficiency and high mechanical performance; however, being excellent in both criteria is uncommon. This review focuses on the principle of material design that was implemented to obtain the self-healing capability of natural rubber from the combination of covalent and non-covalent bonds to obtain an optimal balance between mechanical strength and healing ability. This article also covers the methods that can be applied for self-healing testing and other important characterizations. Potential applications and challenges of self-healing rubber were also discussed. Synthetic rubbers were included in this review for comparison and future strategies.